CoWO4 nanoparticles prepared by two methods displaying different structures and supercapacitive performances. (1st March 2015) - Xing, Xuteng; Gui, Yongliang; Zhang, Guijie; Song, Chunyan
Abstract: The simple wet-chemical and hydrothermal approaches were used to prepare amorphous CoWO4 -amorphous and crystal CoWO4 -crystalline nanoparticles for the electrode materials in supercapacitors. The CoWO4 nanoparticles were characterized and their capacitances were investigated by a three-electrode system. The results showed that specific capacitances for the as-prepared CoWO4 -amorphous and CoWO4 -crystalline were 403 F/g and 264 F/g at the current density of 0.5 A/g. The amorphous structure, small size and narrow particle size distribution contributed to the high electrochemical performances of CoWO4 . In addition, the CoWO4 also showed a low resistance and good cycle-life stability. Therefore, CoWO4 is a very promising electrode material for supercapacitors.